Differential serotonergic modulation of two types of aggression in weakly electric fish - Zubizarreta, Lucía; Perrone, Rossana; Stoddard, Philip K.; Costa, Gustavo; Silva, Ana (Frontiers in Behavioral Neuroscience, 2012)
Agonistic aggression has provided an excellent framework to study how conserved circuits and neurochemical mediators control species-specific and context-dependent behavior. The principal inhibitory control upon aggression is serotonin (5-HT) dependent, and the activation of 5-HT1A receptors is involved in its action. To address whether the serotonergic system differentially regulates different types of aggression, we used two species of weakly electric fish: the solitary Gymnotus omarorum and the gregarious Brachyhypopomus gauderio, which display distinctive types of aggression as part of each species’ natural behavioral repertoire. We found that in the reproduction-related aggression displayed by B. gauderio after conflict resolution, the serotonergic activity follows the classic pattern in which subordinates exhibit higher 5-HT levels than controls. After the territorial aggression displayed by G. omarorum, however, both dominants and subordinates show lower 5-HT levels than controls, indicating a different response of the serotonergic system. Further, we found interspecific differences in basal serotonin turnover and in the dynamic profile of the changes in 5-HT levels from pre-contest to post-contest. Finally, we found the expected reduction of aggression and outcome shift in the territorial aggression of G. omarorum after 8-OH-DPAT (5-HT1A receptor agonist) administration, but no effect in the reproduction-related aggression of B. gauderio. Our results demonstrate the differential participation of the serotonergic system in the modulation of two types of aggression that we speculate may be a general strategy of the neuroendocrine control of aggression across vertebrates.